An Empirical Study of Price Discovery in Commodities Futures Market - Irfan, Mohammad; Hooda, Jayant (Indian Journal of Finance, 2017)
Price discovery is one of the major economic functions of the futures market. It provides a competitive response of futures prices which are derived from spot prices. Basically, aÂ commodity derivative is multifarious in a growing country like India. India is one of the leading producers of agriculture commodities. The main aim of this study was to find out the effectiveness of commodity derivatives in price discovery in agriculture commodities in India. The price discovery relationship of 10 agricultural commodities was investigated. The daily price information of 10 agriculture commodities namely wheat, sugar, chili, mustard-seed, chana (Bengal gram whole), pepper, turmeric, soybean, barley, and maize were taken from NCDEX for the period from 2005 to 2015. The study used simple descriptive statistics, ADF test, PP-test, Johansen co-integration, and Granger causality test to find the answers. We found that there is long-run equilibrium relationship established in 10 commodities. The outcome of the Granger causality test showed unidirectional Granger lead-lag relationships between spot and futures markets in all agricultural commodities in which there were two co-integrations and causality. The findings of the study have important policy and regulatory implications for the Indian commodity futures market. The study will also be helpful to the investors and other market participants to understand the mechanism of the Indian commodity futures market.